Implementation of the Assalamualaikum Dance in Developing Kinesthetic Intelligence of PIAUD Students - -, Rifki Ayu Rosmita (Jurnal Seni Tari, 2024)
This research aims to determine the implementation of the Assalamualaikum Dance in developing the kinesthetic intelligence of students. The study employs a descriptive qualitative approach. The data collection techniques used in this research are observation, interviews, and documentation. The subjects of this study are fifth-semester students from the Early Childhood Education Study Program at UIN Mataram. The data analysis techniques used in this study include data reduction, data display, and conclusion drawing. Based on the data analysis results, it was found that the implementation of the Assalamualaikum Dance was conducted according to the learning objectives to develop students' kinesthetic intelligence. The application of the Assalamualaikum Dance was carried out in the following steps: performing body exercises first, demonstrating movements with counts, demonstrating movements accompanied by music, and conducting movement evaluations. Based on the data obtained, it can be concluded that these activities can develop students' kinesthetic intelligence. It is evident from the movements performed, such as body strength in executing movements, body flexibility in performing movements, body balance during movement, body coordination while moving, and movement skills while dancing.